Ion recognition enables fast Mg–Cl bond dissociation kinetics and better Mg plating/stripping reversibility - Jiacheng Yang; Jinlei Zhang; Kun Zhang; Jing Liu; Zhenfang Zhou; Zhenjiang Li; Guicun Li; Guanglei Cui; Zhonghua Zhang (Journal of Magnesium and Alloys)
Rechargeable Mg-metal batteries hold considerable promise for renewable energy storage and utilization. However, the Mg stripping/plating processes suffer from sluggish ion pairs dissociation kinetics, resulting in poor rate and cycle properties. In this work, an efficient skeleton host containing dissimilar coupling elements with varied electronegativity has been designed to promote interfacial reaction kinetics by accelerating the Mg–Cl bond dissociation process. As a proof-of-concept prototype, the N/O-doped cobalt nanoparticles embedded in carbonaceous polyhedrons has been synthesized via facile high temperature annealing of zeolitic imidazolate framework-67 (ZIF-67). The exposed electron-rich N/O sites and electron-deficient Co sites can regulate the adsorbing structure configuration of [Mg-Cl]+ complex ions by selectively bonding with the Mg2+ and Cl– through chemical coordination linkage, respectively. The elongated bond length from 2.596 Å to 2.679 Å and the weakened bond strength are beneficial for the complex ions dissociation, leading to better charge transfer kinetics. In addition, the better magnesiophilic property accompanied by the conductive and porous permeable three-dimensional architecture realizes the homogeneous electrodeposition of Mg and improved electrode kinetics. The decreased overpotential has been verified in both magnesium organohaloaluminates electrolyte (from 290 mV to 189 mV) and conventional Mg(TFSI)2-based electrolyte (from 600 mV to 200 mV). The designed skeleton host also exhibits excellent long cycle lifespan above 2300 h and extra-high average Coulombic efficiency of 99.65 % within 700 cycles. The accelerated bond splitting strategy enables improved metal-anode reversibility, which is also insightful to high concentrated or other electrolyte systems that contain abundant ion pairs or aggregates.